2022
DOI: 10.7150/ijms.68945
|View full text |Cite
|
Sign up to set email alerts
|

Associations and Interactions between Heavy Metals with White Blood Cell and Eosinophil Count

Abstract: The accumulation of heavy metals in the body has been associated with an elevated immune response. The aim of this study was to investigate the associations among heavy metals and white blood cell (WBC) and eosinophil count in the general population in southern Taiwan. We also explored the interactions and synergetic effects of heavy metals on WBC and eosinophil count. We conducted a health survey in the general population living in southern Taiwan between June 2016 and September 2018. Seven heavy metals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…An epidemiological study in the USA reported that Ellen M. Wells et al observed a significant association of lead with increased eosinophils among non-Hispanic Whites with asthma after control confounding factors [ 52 ]. Additionally, another cross-sectional study involving 2447 participants also observed a positive association between blood Pb concentrations and blood eosinophil counts [ 34 ]. However, this cross-sectional study did not conduct stratified analyses in different populations to verify the stability and reliability of this association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An epidemiological study in the USA reported that Ellen M. Wells et al observed a significant association of lead with increased eosinophils among non-Hispanic Whites with asthma after control confounding factors [ 52 ]. Additionally, another cross-sectional study involving 2447 participants also observed a positive association between blood Pb concentrations and blood eosinophil counts [ 34 ]. However, this cross-sectional study did not conduct stratified analyses in different populations to verify the stability and reliability of this association.…”
Section: Discussionmentioning
confidence: 99%
“…Cd exposure can occur through contaminated water, contaminated food, smoking, and occupational settings [ 53 , 54 ]. In an epidemiological study, Chao-Hsin Huang et al reported that a high concentration of Cd was associated with a high eosinophil count [ 34 ]. Hg is a ubiquitous heavy metal, which is a growing public concern owing to its wide distribution and serious adverse health impacts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…as the immune system is activated in the body with defense mechanism (Sharma, Panwar, & Mogra, 2012). Huang et al (2022)showed the association of heavy metal accumulations in the body with a rise in the immune response by measuring some metals, including lead, in the blood, where a significant increase in the number of WBCs was observed. In addition, lead poisoning causes peripheral and central nervous disorders, encephalopathy and poor coordination.…”
Section: The Percentage Of Carbon Monoxide Gasmentioning
confidence: 99%